UJI EFEKTIVITAS PASTA HENNA BERBAHAN DASAR EKSTRAK DAUN PACAR (LAWSONIA INERMIS) DAN DAUN GAMBIR (UNCARIA GAMBIR) PADA ASPEK KEPEKATAN WARNA DAN DAYA TAHAN PADA KUKU - Christina Hutagalung, Gracede; Sitompul, Astrid; Laurentriana Gea, Sesillia; Annisa Damanik, Pebri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of henna paste formulated from henna (Lawsonia inermis) and gambier (Uncaria gambir) leaf extracts regarding color intensity and durability on fingernails. The study was motivated by the fact that natural henna typically yields less intense color and exhibits variable durability. The inclusion of gambier leaves which contain catechins and tannins was expected to enhance the color quality of natural henna. An experimental method with a pretest-posttest design was employed. The study sample was divided into two groups: 10 panelists used the henna/gambier extract paste, while another 10 panelists used a henna paste containing synthetic dye as a comparison group. Data were collected through observations using a Henna Color Chart, organoleptic testing, and documentation. Data analysis involved descriptive quantitative methods followed by the Mann–Whitney test at a significance level of 0.05. The results showed that color intensity in the henna/gambier extract group fell within the A04–D04 range (predominantly B04), whereas the comparison group fell within the B02–E02 range (predominantly C01). Regarding color durability, the natural henna group showed an average color change of 4.1 levels, compared to 4.4 levels for the comparison group. The Mann–Whitney test yielded a calculated U-value of 42 exceeding the critical U-table value of 23 indicating no significant difference between the two treatment groups. Thus, henna paste based on henna and gambier extracts effectively produces reasonably intense color and offers durability comparable to synthetic-dye-based henna, making it a potential safe and eco-friendly alternative for nail coloring.